European Validation of the Self-Evaluation of Negative Symptoms (SNS): A Large Multinational and Multicenter Study - Dollfus, Sonia; Mucci, Armida; Giordano, Giulia M.; Bitter, István; Austin, Stephen F.; Delouche, Camille; Erfurth, Andreas; Fleischhacker, W. Wolfgang; Movina, Larisa; Glenthøj, Birte; Gütter, Karoline; Hofer, Alex; et al. (Frontiers in Psychiatry, 2022)
Background: Negative symptoms are usually evaluated with scales based on observer ratings and up to now self-assessments have been overlooked. The aim of this paper was to validate the Self-evaluation of Negative Symptoms (SNS) in a large European sample coming from 12 countries. We wanted to demonstrate: 1- good convergent and divergent validities; 2- relationships between SNS scores and patients’ functional outcome; 3- the capacity of the SNS compared to the Brief Negative Symptom Scale (BNSS) to detect negative symptoms; 4- a five-domain construct in relation to the 5 consensus domains (social withdrawal, anhedonia, alogia, avolition, blunted affect) as the best latent structure of SNS. Methods: Two hundred forty-five subjects with a DSM-IV diagnosis of schizophrenia completed the SNS, the Positive and Negative Syndrome Scale (PANSS), the BNSS, the Calgary Depression Scale for Schizophrenia (CDSS), and the Personal and Social Performance (PSP) scale. Results: Significant positive correlations were observed between the total score of the SNS and the total scores of the PANSS negative subscale (r= 0.37; P < 0.0001) and the BNSS (r= 0.43; p <0.0001). SNS scores did not correlate with the level of insight, parkinsonism, or the total score of the PANSS positive subscale. A positive correlation was found between SNS and CDSS (r = 0.35; p < 0.0001). Among the 5 SNS subscores, only avolition subscores entered the regression equation explaining a lower functional outcome. The 1-factor and 2-factor models provided poor fit, while the 5- factor model and the hierarchical model provided the best fit, with a small advantage of the 5-factor model. The frequency of each negative dimension was systematically higher using the BNSS and the SNS versus the PANSS and was higher for alogia and avolition using SNS versus BNSS. Conclusion: In a large European multicentric sample, this study demonstrated that the SNS has: 1-good psychometric properties with good convergent and divergent validities; 2- a five-factor latent structure; 3- a large association with patients’ functional outcome; and 4- the capacity to identify subjects with negative symptoms that is close to the BNSS and superior to the PANSS negative subscale.